Hematologic findings predictive of bone marrow disease in dogs with multicentric large‐cell lymphoma. (19th August 2014) - Graff, Emily C.; Spangler, Elizabeth A.; Smith, Annette; Denhere, Melody; Brauss, Minerva
<x xml:space="preserve">Abstract</x> Background Evaluation of the bone marrow is needed for complete staging in dogs with multicentric large‐cell lymphoma, but is often omitted in clinical practice. Objectives The objective was to determine if routine peripheral blood findings, including microscopic evaluation of blood smears, can predict the presence of bone marrow involvement in dogs with lymphoma. Methods Hematologic data including evaluation of blood smears and bone marrow aspirates from 107 dogs newly diagnosed with large‐cell lymphoma were retrospectively evaluated. Neoplastic lymphocytes were identified based on cell size, nuclear size, chromatin pattern, and the presence of nucleoli. Positive specimens were defined as having ≥ 10% neoplastic lymphocytes. Two groups were established based on the presence or absence of lymphoma in the bone marrow. Variables (positive blood smear, HCT, platelet count, and total and differential WBC counts) were evaluated to determine if they were predictive of bone marrow involvement using univariate and multivariate logistic models. Results Thrombocytopenia and the presence of > 10% neoplastic lymphocytes on blood smears were identified as significant variables for predicting the presence of bone marrow involvement. When considered independently, either a positive blood smear or thrombocytopenia had low sensitivity (60%) and moderate specificity (89% and 87%, respectively). Sensitivity increased when these variables were evaluated together (80%). Conclusions In dogs with multicentric large‐cell lymphoma, thrombocytopenia or the presence of neoplastic lymphocytes in circulation is suggestive of bone marrow involvement, but not definitive. Normal peripheral blood findings do not exclude the possibility of lymphoma in the bone marrow.